The firefly summer - Matson, Morgan (Simon & Schuster Books for Young Readers, 2023)
"For as long as Ryanna Stuart can remember, her summers have been spent with her father and his new wife. Just the three of them, structured, planned, quiet. But this summer is different. This summer, she's received a letter from her grandparents--grandparents neither she nor her dad have spoken to since her mom's death--inviting her to stay with them at an old summer camp in the Poconos. Ryanna accepts. She wants to learn about her mom. She wants to uncover the mystery of why her father hasn't spoken to her grandparents all these years. She's even looking forward to a quiet summer by the lake. But what she finds are relatives... SO MANY MORE RELATIVES than she knew she had. Aunts and Uncles and cousins upon cousins--a motley, rambunctious crew of kids and eccentric, unconventional adults. Lost in the crush of such a tight-knit and boisterous band, Ryanna has never felt more out of place. It's over the course of this utterly astonishing summer that Ryanna will need to learn how to be open to the unexpected, let go of the preconceived, and find where she belongs. And while she's at it, she just may find a way to become part of the Van Camp family camp--for good"--